Can biogas, generated from cattle waste reduce negative externalities? A case of study in argentina - Cristiano, Gabriela; Buitrago, Claudia (Semestre Económico, 2020)
Lately, Argentina has been promoting renewable energies by implementing several programs. Agroindustrial activities generate organic waste, which could be treated to mitigate the negative externalities it causes. In this work the results proposed regarding the volume of biogas generation from waste were estimated for a firm in the Corfo region in the province of Buenos Aires. We present an alternative to reduce negative externalities and improve environment through the transformation of biomass into caloric energy, considering the case of a multiproduct firm, in which waste can be the input to produce a new output (biogas and biofertilizer). We determined that, from the effluent generated by 500 heads of cattle, it is possible to obtain 10.125 m3 of biogas/ month, which could be sold or used by the agrarian firm for self-consumption, diminishing its costs.